DAMPAK ALOKASI DANA DESA TERHADAP PEMBANGUNAN DAN KESEJAHTERAAN MASYARAKAT DESA DI KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Siti Muslihah; Hilda Octavana Siregar; Sriniyati - (Politeknik Negeri Batam, 2019)
This study aimed to determine the impact of village funds on development and welfare in Bantul Regency Special Region of Yogyakarta. The study was conducted by comparing indicators of development and welfare between before and after the village funds. The sample of the study was 75 villages of Bantul Regency. The data analysis used paired sample t-test to saw the impact resulting from the allocation of village funds. The test results showed that there were significant differences in physical development and community welfare between before the existence of village funds and after the village funds were given. These results indicated that the provision of village funds by the government has an impact on physical development and community welfare in the Bantul Regency Special Region of Yogyakarta.